6th International Conference on Solid State Science and Technology & Workshop on Advanced Materials Technology : Growth and Characterization - PPSF, Pusat Pengajian Sains Fizik; INOR, Institut Penyelidikan dan Teknologi Nano Optoelektronik (2017)
Enhancing Dimensional Network of Science & Technology